Relationship Between Family Support and Blood Sugar Control Compliance in Type 2 Diabetes Mellitus Patients at Pekauman Public Health Center Banjarmasin - Nadya, Hesti Elva; Tjomiadi, Cynthia Eka Fayuning; Manto, Onieqie Ayu Dhea (Universitas Ibn Khaldun Bogor, 2025)
Diabetes Mellitus type 2 is a disease in which the body is able to produce insulin but not as much or less than needed. Behavior towards prevention and control depends on family support for compliance with blood sugar control in patients with diabetes mellitus type 2. Emotional support is a very influential support in this study, with emotional support DM patients feel cared for and appreciated in the treatment process. The purpose of this study was to analyze whether there is a relationship between family support and compliance with blood sugar control in patients with diabetes mellitus type 2 at the Pekauman Banjarmasin Health Center. The study used a quantitative method with an analytical design and a cross-sectional approach on 48 respondents with type 2 diabetes mellitus using a purposive sampling technique using a family support questionnaire and diabetes mellitus control. The hypothesis was analyzed using the Spearman Rank test. The results of this study were 32 people (64.0%) with high family support and 42 people (84.0%) adhered to blood sugar control and the results of the hypothesis test showed a p value =0.001 <0.05. It can be concluded that there is a significant correlation between family support and compliance with blood sugar control in type 2 diabetes mellitus sufferers. The higher the support given to members who are sick or in the process of healing their illness, the more positive impact it will have on the health of its members and will give rise to positive behaviors.